(untitled) (MINDEN Journal of History and Archaeology, 2025)
This study examines the economic and trade dynamics of the Han Dynasty’s northern frontier, a region shaped by both conflict and exchange with nomadic groups such as the Xiongnu. It investigates how state economic policies influenced frontier society and its integration with the Han heartland. Drawing on historical records and archaeological evidence, the paper analyzes agricultural colonization, animal husbandry, garrison economies, and official trade markets (guanshi). The findings show that frontier development, though highly militarized, was economically indispensable. Tuntian farming and horse breeding supplied critical resources for defense, while border trade facilitated the exchange of silk, grain, and manufactured goods for steppe horses, furs, and livestock. Despite persistent warfare and economic vulnerability, sustained state investment and tribute–trade systems fostered a hybrid economy that linked agrarian and nomadic networks. The study concludes that the northern frontier was not a peripheral zone but a strategically vital corridor that ensured imperial security, promoted cross-cultural integration, and contributed to the rise of the Silk Road. These insights underscore the central role of economic governance in Han frontier policy and highlight its lasting significance for understanding early Chinese border management before 220 CE. Keywords: Han Dynasty; Northern Frontier; Economy; Trade; Xiongnu